2021
DOI: 10.1055/s-0040-1722649
|View full text |Cite
|
Sign up to set email alerts
|

Fresh Frozen Plasma Transfusion: An Independent Risk Factor for Hemodynamically Significant Patent Ductus Arteriosus in Premature Infants

Abstract: Objective The incidence of patent ductus arteriosus (PDA), a major complication of prematurity, may be reduced by restricting fluid administration. Prophylactic fresh frozen plasma (FFP) transfusion may reduce the incidence of intraventricular hemorrhage in these infants, but risks transfusion-related volume overload. We conducted a retrospective study to investigate whether FFP transfusion is a risk factor for hemodynamically significant PDA (hsPDA) in very low birth weight (BW) premature infants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…The improvement of diuresis observed in the postintervention, although in the normal range in both study periods, further supports the concept that FFP transfusion may worsen cardiac and respiratory performances, namely TACO and TRALI [20,24]. Indeed, FFP use has been identified as an independent risk factor for hemodynamically significant patent ductus arteriosus in preterm neonates due to a fluid management perturbation [25].…”
Section: Discussion/conclusionsupporting
confidence: 71%
“…The improvement of diuresis observed in the postintervention, although in the normal range in both study periods, further supports the concept that FFP transfusion may worsen cardiac and respiratory performances, namely TACO and TRALI [20,24]. Indeed, FFP use has been identified as an independent risk factor for hemodynamically significant patent ductus arteriosus in preterm neonates due to a fluid management perturbation [25].…”
Section: Discussion/conclusionsupporting
confidence: 71%
“…However, De Buyst et al [34] concluded that fluid restriction did not reduce pulmonary circulation overload in their prospective observational study. Additionally, this association is also postulated to be triggered by an increase in prostaglandin E2 levels resulting from excessive fluid intake [35][36][37].…”
Section: Discussionmentioning
confidence: 99%